2020
DOI: 10.3390/ijerph17176210
|View full text |Cite
|
Sign up to set email alerts
|

Source-Specific Volatile Organic Compounds and Emergency Hospital Admissions for Cardiorespiratory Diseases

Abstract: Knowledge gaps remain regarding the cardiorespiratory impacts of ambient volatile organic compounds (VOCs) for the general population. This study identified contributing sources to ambient VOCs and estimated the short-term effects of VOC apportioned sources on daily emergency hospital admissions for cardiorespiratory diseases in Hong Kong from 2011 to 2014. We estimated VOC source contributions using fourteen organic chemicals by positive matrix factorization. Then, we examined the associations between the sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Studies have emphasized the close link between air contaminants and human diseases involving the upper airway, pulmonary, cardiovascular, liver, respiratory, renal, autoimmune, skin, eye diseases, and diabetes. For example, data on VOCs was reported to be positively correlated with emergency hospital visits for chronic obstructive pulmonary diseases [26]. Another report also demonstrated that exposure to VOCs increased the pulmonary health risk through alteration of the gas-liquid interface properties of pulmonary surfactants [27].…”
Section: Air Pollution and Human Diseasesmentioning
confidence: 99%
“…Studies have emphasized the close link between air contaminants and human diseases involving the upper airway, pulmonary, cardiovascular, liver, respiratory, renal, autoimmune, skin, eye diseases, and diabetes. For example, data on VOCs was reported to be positively correlated with emergency hospital visits for chronic obstructive pulmonary diseases [26]. Another report also demonstrated that exposure to VOCs increased the pulmonary health risk through alteration of the gas-liquid interface properties of pulmonary surfactants [27].…”
Section: Air Pollution and Human Diseasesmentioning
confidence: 99%
“…Exposure to environmental factors such as air pollution have previously been suggested to amplify the effect of traditional risk factors, such as blood pressure and smoking [ 1 , 2 ], on cardiovascular risk [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In ambient air, the most significant sources are from vehicle exhausts, while major indoor sources of VOCs include building materials and finishes (primarily flame retardants) such as paints and floor coverings made of, or containing, flexible plastics such as vinyl, engineered wood products, cleaning products and fragranced personal hygiene products [ 5 , 6 ]. Although VOCs detected in indoor environments are usually present at low concentrations, they have been associated with a range of adverse health effects including sensory and skin irritation, headaches, nausea, respiratory illness and cancer [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, exposure to air toxics early in life predisposes children to asthma, one of the most prevalent diseases in this demographic group. Epidemiologic studies have linked prenatal and early life exposure to air toxics with childhood wheeze, asthma, and altered lung function (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Asthma-related medication use, emergency room visits, and hospitalizations are frequently studied asthma outcomes that reflect asthma severity, control, and healthcare utilization (28)(29)(30). While some studies have reported associations between particular air toxics and these asthma subphenotypes (9,11,12), none addressed our goal to identify combinations of air toxics from a large national assessment of air toxics associated with these asthma outcomes. We tested our hypothesis by geocoding levels of 125 air toxic from the US Environmental Protection Agency's (EPA) National Air Toxic Assessment (NATA) (31), one of the richest sources of multi-air toxic profiling across the US, to the residential addresses of children with asthma from our Airway in Asthma (ARIA) study (32) to map each child's exposure to air toxics during the first years of life.…”
Section: Introductionmentioning
confidence: 99%